Partisipasi Anak-anak dalam Perjamuan Kudus: Kajian Teologi Konstruktif terhadap Perjamuan Kudus di Gereja Kristen Protestan Indonesia Melalui Teori Being as Communion Menurut John Zizioulas - Tobing, Vaciel Anna Mishalca; Marpaung, Frans Best Soma (STFT Jakarta, Indonesia, 2025)
This article discusses the involvement of children in Holy Communion at GKPI using the theory of Being as Communion according to John Zizioulas. This article is motivated by the importance of Holy Communion as one of the sacraments that is a gift for all people. However, the GKPI itself as a Lutheran church rejects the idea of children participating in Holy Communion. This article departs from qualitative methods and uses a constructive theology approach, which aims to construct a theological understanding that children are also part of Communio Sanctorum and also participate in Holy Communion. Thus, through the theory of Being as Communion according to John Zizioulas, it can provide a relevant view for the GKPI in understanding Holy Communion for children, because children are also part of the Communio Sanctorum, Holy Communion is God's gift to all people and the experience of faith is not only a matter of theological formulation but also intuitive and emotional matters.